1993
DOI: 10.1128/aac.37.1.19
|View full text |Cite
|
Sign up to set email alerts
|

A point mutation in the human cytomegalovirus DNA polymerase gene confers resistance to ganciclovir and phosphonylmethoxyalkyl derivatives

Abstract: Nature (London) 358:162-164, 1992]. In the present study, we mapped the second mutation to a 4.1-kb DNA fragment containing the DNA polymerase gene and showed that it confers ganciclovir resistance without impairing phosphorylation. Sequence analysis of the 4.1-kb region revealed a single nucleotide change that resulted in a glycine-to-alanine substitution at position 987 within conserved region V of the DNA polymerase. Recombinant viruses constructed to contain the DNA polymerase mutation but not the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
96
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(102 citation statements)
references
References 54 publications
(63 reference statements)
4
96
1
1
Order By: Relevance
“…Experiments showed that cidofovir-PP was 8.5-fold less inhibitory to the cowpox-R (SF) DNA polymerase than it was to cowpox-WT polymerase. Other investigators have determined that human cytomegalovirus resistance to cidofovir was due to mutations in the viral DNA polymerase (29). Thus, it seems likely that orthopoxvirus resistance to cidofovir is due primarily to mutations in the viral DNA polymerase, resulting in a decreased sensitivity of the enzyme to inhibition by cidofovir-PP.…”
Section: Fig 2 Treatment Of Intranasal Infections Withmentioning
confidence: 99%
See 2 more Smart Citations
“…Experiments showed that cidofovir-PP was 8.5-fold less inhibitory to the cowpox-R (SF) DNA polymerase than it was to cowpox-WT polymerase. Other investigators have determined that human cytomegalovirus resistance to cidofovir was due to mutations in the viral DNA polymerase (29). Thus, it seems likely that orthopoxvirus resistance to cidofovir is due primarily to mutations in the viral DNA polymerase, resulting in a decreased sensitivity of the enzyme to inhibition by cidofovir-PP.…”
Section: Fig 2 Treatment Of Intranasal Infections Withmentioning
confidence: 99%
“…Mutations were found in the viral DNA polymerase gene that conferred drug resistance (29,32). Resistance to cidofovir results in cross-resistance to other antiviral drugs (29,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely assumed that in virus-infected cells, the primary enzymatic targets of these drugs are viral DNA polymerases. Indeed, HPMPC-resistant (HPMPC R ) viruses have been isolated in vitro bearing mutations in the DNA polymerase genes of human cytomegalovirus (HCMV), herpes simplex virus (HSV), and human adenovirus (4,17,35). We have also shown that diphosphoryl HPMPC inhibits primer extension and proofreading reactions catalyzed by vaccinia virus (VAC) DNA polymerase in vitro (18).…”
mentioning
confidence: 99%
“…To date, the majority of ganciclovir-resistant isolates are UL97 gene product (phosphokinase) mutants and remain susceptible to cidofovir 5 . Reduced susceptibility to cidofovir, however, has been reported for DNA polymerase mutants of CMV which are resistant to ganciclovir [6][7][8][9] . To date, all clinical isolates which exhibit high level resistance to ganciclovir, due to mutations in both the DNA polymerase and UL97 genes, have been shown to be cross resistant to cidofovir.…”
mentioning
confidence: 99%